Pengaruh Semangat Kerja dan Kualitas Kerja Terhadap Prestasi Kerja pada Karyawan PT Bumi Pasir Putih - Nadia Arnetta; Asmanita Asmanita (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of morale and work quality on work performance of PT Bumi Pasir Putih. Qualitative and quantitative data are the types of data used by researchers. The data in this study was collected using questionnaires distributed to employees at PT. White Sand Earth. In this study also used three variables, namely morale and work quality as independent variables, while work performance as a dependent variable. This research is expected to be a good evaluation and consideration for companies in improving employee performance. The results of the research obtained are morale and work quality has a significant influence on work quality. The results of this study are input for the company to find out how much influence morale and work quality have on work performance so that the company can further improve employee performance in the future.